مسؤولية البنوك في التشريع الجزائري - غريب, وردة (Universté ELOUEd-جامعة الوادي, 2023)
إن حداثة النظام البنكي الجزائري، جعلته يفتقر إلى آليات عمل تكفل له مسايرة التوجهات الاقتصادية في ظل الانفتاح الواسع لاقتصاد السوق، وعولمة مالية متزايدة سمتها الأساسية اندماج الأسواق المالية الدولية وترابطها ، وفي ظل تطور الجريمة المتعلقة بالأعمال المصرفية أقدم المشرع الجزائري على جملة من الإصلاحات وتوجت بإصدار ترسانة من القوانين معترفا بالمسؤولية الجزائية للشخص المعنوي ، إلا أن هذه الإصلاحات لم تؤتي أكلها إلى حد الساعة ، ولكن يجب أيضا الإشارة إلى أن غزارة النصوص القانونية لا تكفي وحدها بل يجب موازاة مع ذلك تطوير آليات عمل النظام البنكي الجزائري.The novelty of the Algerian banking system, lacked mechanisms to ensure that it cope with economic trends in light of the great openness of the market economy, and the increase of financial globalization, its characteristic the integration and interdepended of international financial markets Given the development of organized crime, including money laundering, banks have become an effective tool used by criminals to legitimize the proceeds of their crimes, so the Algerian legislator has tried to find solutions to deal with the crime of money laundering mechanisms such as the placement of bonds to banks to banks investigate suspicious transaction and change the notification of the compromise, in addition to reducing obstacles to bank secrecy, but it should be noted that the abundance of texts are not enough to deal with the phenomenon of money laundering but must be parallel to the development of the mechanisms of the Algerian banking system.
مذكرة الماستر
Keywords: : المسؤولية الجزائية، الشخص المعنوي، المصرف، الاقتصاد.; criminal liability, the legal person, the bank, economy.